Immunopeptidomics and Peptide Expression Profiles to Develop T-Cell Receptors Against Glioma-Associated Antigens. (1st September 2019) - Carrera, Diego A; Hayes, Josie; Müller, Sören; Watchmaker, Payal; Shelton, Samuel; Hilf, Nolbert; Weinschenk, Toni; Schoor, Oliver; Kohanbash, Gary; Oldham, Michael; Costello, Joseph; Singh, Harpreet; et al.
Abstract: INTRODUCTION: Diffuse infiltrating low-grade gliomas (WHO grade II and III) are slow-growing primary brain tumors, but considered malignant due to their invasive growth and inexorable malignant progression at recurrence. Highly personalized immunotherapies are currently a challenging endeavor, due to the low mutational load of gliomas, as described by various neoantigen discovery pipelines. Hence, it is important to extend our antigen search to other gene alterations such as alternative splicing or target epitopes derived from proteins that are absent in normal tissues. The purpose of this study is to address this gap and increase the available repertoire of T-cell receptors to target in gliomas. METHODS: In the current study, we start by analyzing a set of 64 peptides derived from nonmutated proteins reported by Hilf et al (Nature, 2019) as part of their actively personalized vaccination trial. These were isolated from the human leukocyte antigen (HLA)-A*02:01 and A*24:02 molecules of primary glioblastoma tissues. The initial screening for immunogenic targets was performed assessing datasets of RNA expression levels in normal brain and peripheral organs and measure the differential expression in primary gliomas paired with their corresponding recurrent tumors. RESULTS: We find 3 antigen epitopes being exclusively expressed in gliomas that increase their expression at recurrence, without significant levels in normal tissues. Furthermore, we report an epitope derived from a tumor-specific isoform, which we use to stimulate healthy-donor PBMCs and isolate reactive CD8+ T-cells to sequence their T-cell receptor and engineer patient-derived T-cells against this target. CONCLUSION: Our results suggest that cell-based immunotherapies targeting these epitopes can be highly effective and safe, reducing the likelihood of adverse events, effectively addressing tumor heterogeneity and interpatient variability. Moreover, this is the first successful attempt to target an epitope derived from a tumor-specific isoform in glioma with an engineered T-cell receptor.